A study on temperature characteristics of green silicon photodetector - Xiansong, Fu; Suying, Yao; Yunguang, Zheng; Yang, Yan; Tao, Ge; Maolin, De (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Green silicon photodetector is successfully developed on the substrate of n-type single-crystal (100) silicon. To improve its performance, the detector is optimized by optimizing the p-n junction depth xj and the thickness of antireflection layer to reduce dark current, shorten response time and increase sensitivity. The spectrum response SNR can be over 104 within the wavelength range of 500–600 nm and the peak of spectral responsivity is 0.48 A/W at about 520 nm. The temperature characteristics of the dark current at reverse bias and photocurrent at zero bias are emphatically investigated. Firstly, the temperature behavior of dark current at 10 V reverse bias voltage and temperature range of 253–323 K is studied. Results show that dark current is dominated by generation-recombination current Igr the temperature range of 253–283 K and it is dominated by traps tunneling current Itt at the temperature range of 283–323 K. Secondly, the temperature behavior of photocurrent at zero bias and temperature range of 213–353 K is discussed. Results show that photocurrent increases as temperature increases below room temperature and almost holds the line over room temperature. Consequently, photodetector fulfils quality requirements.
Optica Applicata, Vol. 40, 2010, nr 4, s. 935-941
Keywords: optyka; green silicon photodetector; temperature characteristics; dark current; generation-recombination current; traps tunneling current